Analysis on a 77 GHz MIMO Radar for Touchless Gesture Sensing - Liu, Jingtao; Gu, Changzhan; Zhang, Yueping; Mao, Jun-Fa (IEEE sensors letters, 2020)
This letter presents a novel analysis on a millimeter-wave 77 GHz multiple-input multiple-output (MIMO) radar with virtual antenna array for touchless gesture sensing for human-computer interaction. The virtual array allows fewer receiving channels to achieve higher spatial resolution, which facilitates the integration of radar technology into compact devices. The theoretical analysis and working principles were introduced. Compared to the conventional analysis of MIMO radar, the analytical model proposed in this letter takes the radiation pattern of each antenna into consideration and reveals the nature of virtual antenna array, e.g., the change of the phase factor. Besides, the radiation pattern of each virtual antenna is also obtained, and two equivalent virtual array models decomposed by the analytical model are also discussed. A 77 GHz 2 × 2 MIMO radar system was designed with a maximum scanning bandwidth of 5 GHz and was employed to validate the application of gesture sensing. Based on frequency-modulated continuous-wave with 4 GHz bandwidth and pulse repetition time of 6 ms, a hand's moving gestures were successfully captured with submillimeter accuracy. Presence detection was also experimentally carried out to detect the approach of the subject person.